Posttreatment Low‐Risk Drinking as a Predictor of Future Drinking and Problem Outcomes Among Individuals with Alcohol Use Disorders: A 9‐Year Follow‐Up. (7th February 2017) - Kline‐Simon, Andrea H.; Litten, Raye Z.; Weisner, Constance M.; Falk, Daniel E.
Abstract : Background: Treatment for alcohol use disorders (AUDs) has traditionally been abstinence oriented, but new research and regulatory guidelines suggest that low‐risk drinking may also be an acceptable treatment outcome. However, little is known about long‐term outcomes for patients who become low‐risk drinkers posttreatment. This study explores a posttreatment low‐risk drinking outcome as a predictor of future drinking and psychosocial outcomes over 9 years. Methods: Study participants were adults with AUDs at treatment entry who received follow‐up interviews 6 months posttreatment intake ( N = 1, 061) in 2 large randomized studies conducted at Kaiser Permanente Northern California, a large private, nonprofit, integrated health system. Six‐month drinking status was defined as abstinent, low‐risk (nonabstinent, no 5+ drinking days), or heavy drinking (1 or more days of 5+ drinks). Using logistic regression models, we explored the relationship between past 30‐day drinking status at 6 months and odds of being abstinent or a low‐risk drinker (compared to heavy drinking), and positive Addiction Severity Index psychosocial outcomes over 9 years (9‐year follow‐up rate of 73%). Results: Abstainers and low‐risk drinkers at 6 months had higher odds of recent abstinence/low‐risk drinking over 9 years than heavy drinkers; abstainers had better drinking outcomes than low‐risk drinkers. Additionally, among those with interview data, 95% of abstainers and 94% of low‐risk drinkers at 6 months were abstinent/low‐risk drinkers at 9 years; surprisingly, 89% of heavy drinkers at 6 months were also abstinent/low‐risk drinkers although still significantly fewer than the other groups. Abstainers and low‐risk drinkers at 6 months had better psychiatric outcomes, and abstainers had better family/social outcomes than heavy drinkers; medical outcomes did not differ. Low‐risk drinkers and abstainers showed no reliable differences across psychosocial measures. Conclusions: The findings suggest that a low‐risk drinking outcome may be reasonable over the long‐term for some alcohol‐dependent individuals receiving addiction treatment. Abstract : Individuals who became low‐risk drinkers after treatment were able to maintain positive psychosocial outcomes over 9 years comparable to individuals who remained abstinent, suggesting that the inclusion of low‐risk drinking may be a reasonable treatment outcome in addition to abstinence. Furthermore, all groups (including heavy drinkers) had similar and highly favorable drinking outcomes by the 9‐year follow‐up. This suggests that long‐term drinking outcomes, as compared to psychosocial outcomes, may not be the most ideal way to operationalize long‐term recovery.